The cake bible - Beranbaum, Rose Levy; Wolston, Woody (William Morrow, an imprint of HarperCollinsPublishers, 2024)
Providing countless solutions and tips for commonly encountered baking problems, this updated and expanded cake cookbook provides precise instructions for baking and decorating spectacular special-occasion cakes of any size.